Factors Influencing the Clinical Nursing Risk Management of Professional Nurses in the Operating Room at Center Hospital in the Northeast - Asanam, Pattarapan; Dapa, Somprathana (Medical Journal of Sakon Nakhon Hospital, 2024)
The objective of this research was to study the factors influencing the clinical nursing risk management of professional nurses in the operating room at center hospital in the northeastern region. Data were collected from 230 professional nurses who have worked in the operating room for over a year were included in this study by a multi–stage sampling. The research instrument was a set of questionnaires cosisited of four parts; 1) demographic data of sample 2) attitude towards clinical risk management 3) participative administration and 4) clinical risk management. The content validity was explored by the 5 experts. The reliabilities tested using the Cronbach’s alpha coefficients were 0.88, 0.95 and 0.95, respectively. Data were analyzed by the frequency, percentage, average and stepwise multiple regression analysis. The results revealed that.1) the levels of clinical nursing risk Management of professional nurses in the operating room at the center hospital in the northeast was at the high level ( = 3.92, S.D. = 0.37) 2) The participative and attitude were a moderately positive correlations with clinical risk management of professional nurses in the operating room (r = 0.664, r = 0.580).The period of work in the operating room were are low positive relationship with the clinical risk management of professional nurses in the operating room (r = 0.217) 3)The participative management could predict the clinical risk management of professional nurses at p < 0.01 that participative management attitude and The period of work in the operating room accounted at 51 percent.